Icariin reduces α-synuclein over-expression by promoting α-synuclein degradation - Zhang, Lan (Age (Dordr), 2015)
The objectives of this study are to investigate the effects of icariin (a main component extracted from Epimedium) on over-expression of α-synuclein and to explore the underlying mechanisms. APPV717I transgenic (Tg) mice and A53T α-synuclein-transfected PC12 cells were used in this study. The content of α-synuclein mRNA was determined by reverse-transcription PCR (RT-PCR). Western blotting and immunohistochemistry were used to detect the protein expression of α-synuclein, parkin, ubiquitin carboxy-terminal hydrolase L1 (UCH-L1), and heat shock protein 70 (HSP70). In 10-month-old APP Tg mice, α-synuclein expression was increased, and the expression of Parkin, UCH-L1, and HSP70 was decreased in the hippocampus. Intragastrical administration of icariin (30 and 100 μmol/kg) for 6 months (from 4 to 10 months old) decreased α-synuclein expression and increased the expression of Parkin, UCH-L1, and HSP70 in the hippocampus of APP Tg mice. Incubation of icariin (40 and 80 μM) with A53T α-synuclein-transfected PC12 cells for 24 h showed no difference in the expressions of α-synuclein mRNA among model group and icariin-treated groups, but decreased α-synuclein protein expression in both monomer and tetramer. Along with the downregulation of α-synuclein, icariin (40 and 80 μM) elevated the expression of Parkin, UCH-L1, and HSP70 in A53T α-synuclein-transfected cells. Icariin inhibited the over-expression of α-synuclein both in vivo and in vitro. The mechanism of icariin may be related to upregulate Parkin and UCH-L1 expression in ubiquitin-proteasome system and HSP70 in molecular chaperone, thus enhancing the degradation of α-synuclein. It is suggested that icariin may have the potential to treat Alzheimer’s disease (AD) and other synucleinopathies.